Coexistence of Borrelia spp. with different tick-borne pathogens in Ixodes ricinus ticks removed from humans in Poland - Julia Koczwarska; Justyna Polaczyk; Wiktoria Wieczorek; Olga Zdzienicka; Julia Żórańska; Agnieszka Pawełczyk; Renata Welc-Falęciak (Scientific Reports)
Abstract Ixodes ricinus tick is a primary vector of Borrelia spirochetes and various tick-borne pathogens in Europe. Multi-species infections are common among ticks, however, the mechanism by which Borrelia spp. coexists with other pathogens within the tick vector is poorly understood. Furthermore, the extent to which Borrelia spp. interact with other pathogens or how multi-species infections influence pathogen loads in ticks and consequently, their transmission success and pathogenicity, remains unclear. The aim of this study was to evaluate the impact of co-infections on occurrence and loads of Borrelia spp. and other pathogens in I. ricinus. In the years 2021–2022, we collected 2073 I. ricinus ticks from tick-bitten individuals from around Poland and analyzed individually for the presence of Borrelia spp., Rickettsia spp., Neoehrlichia mikurensis, Anaplasma phagocytophilum, Babesia spp. and Bartonella spp. using molecular methods. Loads of pathogens were determined with droplet digital PCR technique. Of the 324 ticks positive for Borrelia spp., 76 were co-infected with at least one different pathogen. We observed higher prevalence of Babesia spp. and N. mikurensis among Borrelia spp. – positive ticks than in ticks uninfected with Borrelia spp. (3.4% vs. 1.3% and 10.2% vs. 4.2% respectively). A similar positive correlation was observed between Babesia spp. and N. mikurensis. Additionally, the loads of N. mikurensis were nearly twice as high in Babesia spp. – positive ticks compared to those not infected with this pathogen. This study is among the first to explore influence of co-infections on pathogen loads in multi-infected ticks feeding on humans. Understanding the relationships between pathogens coexisting in ticks may broaden our insight into epidemiology of tick-borne diseases.